High melting point high viscosity fischer-tropsch wax and method for making same

CN122326277BActive Publication Date: 2026-10-09QINGDAO SINOPLAS HI-NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610468632.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-10
Publication Date
2026-10-09
Estimated Expiration
2046-04-10

AI Technical Summary

Technical Problem

[0005]为了解决现有技术中传统费托蜡因碳链高度直链化而导致的高熔点往往伴随低粘度,在下游热加工应用中容易发生高温流淌、渗油以及内聚剥离强度不足等技术问题,本发明提出了一种高熔点高粘度费托蜡及其制备方法

Benefits of technology

(1)现有技术在提升费托蜡粘度时易造成结晶体系破坏,导致产物熔点显著下降。本发明通过引入具有介孔-大孔分级孔道结构的锆掺杂硅酸铝分子筛载体和Pt-Re-Sn三元活性组分的双功能催化剂,实现长链烷烃的脱氢微交联与适度支化,并通过多级短程分子蒸馏剔除低碳轻组分。该方法能够在保持产物121℃以上高熔点特性的同时,显著提高分子链间的物理缠结力和熔融态运动粘度,进而提高其内聚力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of fine chemical and petroleum chemical derivative preparation, and particularly discloses high-melting-point high-viscosity Fischer-Tropsch wax and a preparation method thereof. The preparation method of the high-melting-point high-viscosity Fischer-Tropsch wax comprises the following steps: heating and melting Fischer-Tropsch wax raw materials and performing vacuum degassing treatment; mixing the degassed materials with hydrogen-containing mixed carrier gas, and feeding the mixed materials into a fixed bed reactor filled with a bifunctional catalyst to perform reaction; feeding the reaction product mixed with hydrogen into a fixed bed hydrogenation reactor to perform hydrogenation reaction under the action of a hydrogenation saturation catalyst; and introducing the hydrogenation saturation product into a multi-stage short-path molecular distillation device to perform fraction cutting, collecting high-boiling-point heavy components, and cooling and forming to obtain the high-melting-point high-viscosity Fischer-Tropsch wax. When the high-melting-point high-viscosity Fischer-Tropsch wax prepared by the application is applied to hot melt adhesive and a high polymer blending system, the high-temperature overflow and oil seepage phenomena in a molten state can be effectively avoided, and the peeling strength and cohesion of the finally prepared composite material can be significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fine chemical and petrochemical derivative preparation technology, specifically to a high-melting-point, high-viscosity Fischer-Tropsch wax and its preparation method. Background Technology

[0002] Fischer-Tropsch synthesis is the core process for converting coal, natural gas, or biomass into liquid or solid hydrocarbons via syngas. The high-carbon-number solid product produced is Fischer-Tropsch wax. Traditional Fischer-Tropsch waxes are characterized by a highly linear carbon chain structure, regular molecular arrangement, and high crystallinity. Based on this highly symmetrical molecular configuration, traditional Fischer-Tropsch waxes exhibit a high melting point and high room-temperature hardness.

[0003] However, due to the lack of branches in the molecular chains of traditional Fischer-Tropsch waxes and the absence of cross-linking and physical entanglement between the molecular chains, the molecular friction between the long carbon chains is relatively low when in the molten state. This physical property results in a low kinematic viscosity of traditional Fischer-Tropsch waxes in the molten state, typically only 10-20 mm² / s. In industrial applications, when used as hot melt adhesives, specialty coatings, and polymer processing aids, this combination of high melting point and low viscosity leads to application limitations: high-temperature flow and oil seepage are prone to occur under high-temperature processing or application conditions. More importantly, the highly linear wax molecules cannot form effective interpenetration with polymer substrates (such as EVA and polyurethane), resulting in reduced cohesive strength of the blend system and a significant decrease in the adhesion and peel strength of the final product.

[0004] The physical limitation of high melting point usually accompanied by low viscosity has been a drawback of existing technologies. Current thickening methods often involve adding thickening resins or other polymers, but this affects the purity of the system and significantly increases production costs; alternatively, deep oxidative crosslinking methods are used, but this significantly reduces the whiteness of Fischer-Tropsch wax and lowers its high melting point characteristics. Based on the above, this invention proposes a high-melting-point, high-viscosity Fischer-Tropsch wax and its preparation method. Summary of the Invention

[0005] To address the technical problems of traditional Fischer-Tropsch waxes, which often have high melting points but low viscosity due to highly linear carbon chains, leading to issues such as high-temperature flow, oil seepage, and insufficient cohesive peel strength in downstream thermal processing applications, this invention proposes a high-melting-point, high-viscosity Fischer-Tropsch wax and its preparation method.

[0006] In a first aspect, the present invention provides a method for preparing high-melting-point, high-viscosity Fischer-Tropsch wax, employing the following technical solution: A method for preparing a high-melting-point, high-viscosity Fischer-Tropsch wax includes the following steps: S1. The Fischer-Tropsch wax raw material is heated, melted, and then degassed under vacuum to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas and fed into a fixed-bed reactor packed with a bifunctional catalyst to react and obtain the reaction product. S3. After mixing the reaction products with hydrogen, the mixture is fed into a fixed-bed hydrogenation reactor and hydrogenation reaction is carried out under the action of a hydrogenation saturated catalyst to obtain hydrogenation saturated products. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus for fractionation, and the remaining high-boiling-point heavy components are collected, cooled and shaped to obtain high-melting-point, high-viscosity Fischer-Tropsch wax.

[0007] Preferably, in step S1, the heating and melting conditions are: temperature 125-145℃, stirring speed 100-200r / min, and heating time 0.5-1h.

[0008] Preferably, in step S1, the vacuum degassing conditions are: temperature 130-150℃, vacuum degree 3-8kPa, and degassing time 1-2h.

[0009] Preferably, in step S2, the bifunctional catalyst includes a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure, and a Pt-Re-Sn ternary active component supported on the support.

[0010] In this invention, the Pt-Re-Sn ternary active components exhibit a synergistic effect. Pt provides primary active sites for the dehydrogenation of long-chain alkanes to olefins; Re significantly enhances the anti-carbon deposition ability of the metal components, maintaining the stable lifetime of the catalyst in the heavy wax reaction system; and Sn modulates the d-band electronic structure of Pt, weakening its hydrogenolysis activity on C-C bonds. This active component effectively suppresses the decrease in melting point caused by the reduction in molecular weight while achieving micro-crosslinking in heavy Fischer-Tropsch long-chain dehydrogenation.

[0011] Preferably, the bifunctional catalyst is prepared by the following method: (1) Tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride are dissolved in hydrochloric acid aqueous solution, and then macroporous template agent and mesoporous template agent are added in sequence. After stirring and hydrolyzing at 35-45℃ for 2-4h, the mixture is transferred to a reaction vessel and hydrothermally crystallized at 100-120℃ for 30-36h. The product is washed, dried and calcined to obtain zirconium-doped aluminum silicate molecular sieve support with mesoporous-macroporous hierarchical pore structure. (2) Using the ultrasonic-assisted complexation co-impregnation method, chloroplatinic acid, perrhenic acid, stannous chloride and citric acid are dissolved together in hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution is ultrasonically impregnated and mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). After rotary evaporation, drying and calcination and reduction, a bifunctional catalyst is obtained.

[0012] In this invention, a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure is prepared. The macroporous structure effectively eliminates the steric hindrance of diffusion of ultra-long carbon chain (C50+) macromolecules, while the mesopores provide suitable catalytic confinement space. At the same time, zirconium doping modulates the acidity of the molecular sieve, introducing moderately strong Lewis acid sites, avoiding deep cracking caused by strong Brønsted acids. This allows long-chain monoolefins or dienes produced by dehydrogenation to undergo mild intermolecular double bond addition and oligomerization reactions within the mesoporous confinement space, bridging the straight-chain hydrocarbon skeleton and forming a micro-crosslinked and micro-branched network in situ.

[0013] Preferably, in step (1), the mesoporous template agent is hexadecyltrimethylammonium bromide.

[0014] Preferably, in step (1), the macroporous template agent is polystyrene cross-linked divinylbenzene.

[0015] Preferably, in step (1), the concentration of the hydrochloric acid aqueous solution is 1-2 mol / L.

[0016] Preferably, in step (1), the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent is 35-45:6-8:3-4:120-140:3-7:8-12.

[0017] Preferably, in step (1), the washing conditions are: washing with deionized water and anhydrous ethanol alternately until neutral.

[0018] Preferably, in step (1), the drying conditions are: vacuum drying at a temperature of 80-100℃ for 16-20h.

[0019] Preferably, in step (1), the roasting temperature is 500-600℃ and the roasting time is 4-6h.

[0020] Preferably, in step (2), the concentration of the hydrochloric acid aqueous solution is 0.5-1 mol / L.

[0021] Preferably, in step (2), the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride, citric acid and hydrochloric acid aqueous solution is 1-2:0.3-0.5:0.4-0.8:3-5:60-80.

[0022] Preferably, in step (2), the ultrasonic power is 350-450W, the ultrasonic frequency is 40-50kHz, and the immersion time is 2-4h.

[0023] Preferably, in step (2), the rotary evaporation conditions are: temperature 60-80℃, pressure 0.05-0.1MPa, and time 1-2h.

[0024] Preferably, in step (2), the drying temperature is 100-120℃ and the drying time is 10-12h.

[0025] Preferably, in step (2), the roasting temperature is 460-480℃ and the roasting time is 4-6h.

[0026] Preferably, in step (2), the reduction conditions are: reduction at 380-400℃ for 2-3 hours in a hydrogen atmosphere.

[0027] Preferably, in step S2, the reaction conditions are: temperature 300-340℃, reaction pressure 0.1-0.5MPa, and liquid hourly space velocity 1-2h. -1 The volume ratio of hydrogen-containing mixed carrier gas to degassed material is 150-250:1.

[0028] Preferably, the hydrogen-containing carrier gas is composed of a mixture of hydrogen and nitrogen in a volume ratio of 1:4-6.

[0029] Preferably, in step S3, the hydrogenation saturation catalyst is a nickel-molybdenum catalyst or a nickel-tungsten catalyst.

[0030] Preferably, in step S3, the hydrogenation reaction conditions are: temperature 220-240℃, hydrogen pressure 5-7 MPa, and liquid hourly space velocity 1.5-2.5 h⁻¹. -1 The hydrogen-to-oil volume ratio is 400-500:1.

[0031] Preferably, in step S4, the multi-stage short-path molecular distillation apparatus includes a first-stage wiped-film evaporator and a second-stage wiped-film evaporator connected in series.

[0032] Preferably, the operating conditions of the primary scraped film evaporator are: evaporation temperature 210-230℃, vacuum degree 8-15Pa, and scraper rotation speed 150-250r / min.

[0033] Preferably, the operating conditions of the secondary scraped film evaporator are: evaporation temperature 260-280℃, vacuum degree 2-4Pa, and scraper rotation speed 200-300r / min.

[0034] Preferably, in step S4, the high-boiling-point recombinant component refers to micro-crosslinked high-carbon-number isoalkanes with a carbon number ≥ C35.

[0035] In this invention, short-path molecular distillation, due to its shorter heating time, can prevent micro-crosslinked macromolecules from undergoing secondary thermal decomposition at high temperatures, ensuring the complete preservation of high-melting-point, high-viscosity heavy components.

[0036] Preferably, in step S4, cooling and molding refers to: using a condensation crystallization slicer or a steel strip granulator to cool and solidify into flakes or granules.

[0037] Preferably, the specific conditions for the cooling and molding process are as follows: When using a condensation crystallization slicer, the feed temperature is 165-175℃, the cooling water temperature is 15-25℃, and the drum speed is 3-8 r / min to obtain sheet-like products. When using a steel belt granulator, the dripping temperature is 165-175℃ and the cooling zone water temperature is 15-25℃ to produce granular products.

[0038] In this invention, for heavy micro-crosslinked products with high melting point and high viscosity, the feeding or dripping temperature is controlled at 165-175℃. This ensures that the material has sufficient fluidity for coating or dripping, while avoiding molding difficulties and increased cooling energy consumption caused by excessively high temperatures.

[0039] Secondly, the present invention provides a high-melting-point, high-viscosity Fischer-Tropsch wax, employing the following technical solution: A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the above-described method for preparing high-melting-point, high-viscosity Fischer-Tropsch wax.

[0040] In summary, the present invention has the following beneficial effects: (1) Existing technologies tend to damage the crystallization system when increasing the viscosity of Fischer-Tropsch wax, leading to a significant decrease in the melting point of the product. This invention introduces a bifunctional catalyst consisting of a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure and a Pt-Re-Sn ternary active component to achieve dehydrogenation micro-crosslinking and moderate branching of long-chain alkanes, and removes low-carbon light components through multi-stage short-path molecular distillation. This method can significantly improve the physical entanglement force between molecular chains and the kinematic viscosity of the melt while maintaining the high melting point of the product above 121°C, thereby improving its cohesive force.

[0041] (2) Through the action of a bifunctional catalyst, the highly linear Fischer-Tropsch heavy alkanes undergo catalytic dehydrogenation while forming a covalent micro-crosslinked network and branched structure based on the olefin oligomerization mechanism. This effectively enhances the physical entanglement and steric hindrance between carbon chains, increases the kinematic viscosity of the product at 140°C, and solves the technical defects of traditional Fischer-Tropsch wax with both high melting point and low viscosity.

[0042] (3) The present invention involves saturating hydrogenation and multi-stage short-path molecular distillation of the micro-crosslinked reaction product obtained in step S2. The hydrogenation reaction saturates the olefin bonds and chromophores generated by dehydrogenation or micro-crosslinking, ensuring the thermal stability and whiteness of the product; the multi-stage short-path molecular distillation removes low-carbon components with plasticizing effect under short-term heating conditions, effectively retaining the high melting point characteristics of the product and maintaining a low penetration.

[0043] (4) When the high melting point and high viscosity Fischer wax prepared by the present invention is applied to hot melt adhesives and polymer blends, it can reduce the occurrence of high temperature flow and oil seepage in the molten state; at the same time, the micro-crosslinking and branched structure within the molecule enhances the molecular entanglement effect with the polymer substrate, thereby improving the final peel strength and cohesion of the composite material. Detailed Implementation

[0044] The present invention will be further described in detail below with reference to the embodiments.

[0045] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0046] Among them, the Fischer-Tropsch wax raw material, item number FT-WL115, brand Future Energy, was purchased from Jiangsu Runfeng New Materials Co., Ltd.

[0047] Nickel-molybdenum catalyst: Nickel-molybdenum hydroconversion desulfurization catalyst, spherical shape, product size 3-5mm, item number DC-5, brand Shandong Dengzhuo, purchased from Tianjin Kaite New Material Technology Co., Ltd.

[0048] Cross-linked divinylbenzene polystyrene: CAS No. 69011-14-9, brand Kramar, purchased from Shanghai Koraman Reagent Co., Ltd.

[0049] Examples 1-3 provide a high melting point, high viscosity Fischer-Tropsch wax.

[0050] Example 1 A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 125°C and 100 r / min for 1 hour, and then vacuum degassed at 130°C and 3 kPa for 2 hours to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas mixture (composed of hydrogen and nitrogen in a volume ratio of 1:4) and then fed into a fixed-bed reactor packed with a bifunctional catalyst. The reaction is carried out at a temperature of 300℃, a reaction pressure of 0.1MPa, and a liquid hourly space velocity of 1h. -1 The reaction was carried out under the condition that the volume ratio of nitrogen to degassed material was 150:1 to obtain the reaction product. S3. The reaction products are mixed with hydrogen and fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the reaction proceeds at a temperature of 220°C, a hydrogen pressure of 5 MPa, and a liquid hourly space velocity of 1.5 h⁻¹. -1 The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 400:1 to obtain a hydrogenated saturated product. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus (including a first-stage and a second-stage scraped film evaporator connected in series) for fractionation. The evaporation temperature of the first-stage scraped film evaporator is controlled at 210℃, the vacuum degree is 8Pa, and the scraper speed is 150r / min. The evaporation temperature of the second-stage scraped film evaporator is controlled at 260℃, the vacuum degree is 2Pa, and the scraper speed is 200r / min. The remaining high-boiling-point heavy components are collected and granulated using a steel belt granulator. The dripping temperature is controlled at 165℃, and the water temperature in the cooling zone is controlled at 15℃. The granules are cooled and solidified into high-melting-point, high-viscosity Fischer-Tropsch wax.

[0051] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent and polystyrene cross-linked divinylbenzene as a macroporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent to be 35:6:3:120:3:8, dissolving tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride in 1 mol / L hydrochloric acid aqueous solution, then adding macroporous template agent and mesoporous template agent in sequence, stirring and hydrolyzing at 35°C for 4 h, then transferring to a reaction vessel and hydrothermally crystallizing at 100°C for 36 h, washing the product alternately with deionized water and anhydrous ethanol until neutral, drying under vacuum at 80°C for 20 h, and calcining at 500°C for 6 h to remove the template agent, thus obtaining a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure; (2) An ultrasonic-assisted complexation co-impregnation method was adopted, and the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride, citric acid and hydrochloric acid aqueous solution was controlled to be 1:0.3:0.4:3:60. Chloroplatinic acid, perrhenic acid, stannous chloride and citric acid were dissolved together in 0.5 mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). The mixture was impregnated for 4 h at an ultrasonic power of 350 W and an ultrasonic frequency of 40 kHz. The mixture was then rotary evaporated for 2 h at a temperature of 60 °C and a pressure of 0.05 MPa to remove moisture. The mixture was dried at a temperature of 100 °C for 12 h, calcined at 460 °C for 6 h, and finally reduced at 380 °C for 3 h in a hydrogen atmosphere to obtain a bifunctional catalyst.

[0052] Example 2 A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 135°C and 150 r / min for 0.8 h, and then vacuum degassed at 140°C and 5 kPa for 1.5 h to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas mixture (composed of hydrogen and nitrogen in a volume ratio of 1:5) and then fed into a fixed-bed reactor packed with a bifunctional catalyst. The reaction is carried out at a temperature of 320℃, a reaction pressure of 0.3MPa, and a liquid hourly space velocity of 1.5h⁻¹. -1 The reaction was carried out under the condition that the volume ratio of nitrogen to degassed material was 200:1 to obtain the reaction product. S3. The reaction products are mixed with hydrogen and fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the reaction is carried out at a temperature of 230°C, a hydrogen pressure of 6 MPa, and a liquid hourly space velocity of 2 h⁻¹. -1 The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 450:1 to obtain a hydrogenated saturated product. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus (including a first-stage and a second-stage scraped film evaporator connected in series) for fractionation. The evaporation temperature of the first-stage scraped film evaporator is controlled at 220°C, the vacuum degree is 12Pa, and the scraper speed is 200r / min. The evaporation temperature of the second-stage scraped film evaporator is controlled at 270°C, the vacuum degree is 3Pa, and the scraper speed is 250r / min. The remaining high-boiling-point heavy components are collected and granulated using a steel belt granulator. The dripping temperature is controlled at 170°C, and the water temperature in the cooling zone is controlled at 20°C. The granules are cooled and solidified into high-melting-point, high-viscosity Fischer-Tropsch wax.

[0053] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent and polystyrene cross-linked divinylbenzene as a macroporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent to be 40:7:3.5:130:5:10, dissolving tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride in 1.5 mol / L hydrochloric acid aqueous solution, then adding macroporous template agent and mesoporous template agent in sequence, stirring and hydrolyzing at 40°C for 3 h, then transferring to a reaction vessel and hydrothermally crystallizing at 110°C for 33 h, washing the product alternately with deionized water and anhydrous ethanol until neutral, drying under vacuum at 90°C for 18 h, and calcining at 550°C for 5 h to remove the template agent, thus obtaining a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure; (2) An ultrasonic-assisted complexation co-impregnation method was adopted, and the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride, citric acid and hydrochloric acid aqueous solution was controlled to be 1.5:0.4:0.6:4:70. Chloroplatinic acid, perrhenic acid, stannous chloride and citric acid were dissolved together in 0.8 mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). The mixture was impregnated for 3 h at an ultrasonic power of 400 W and an ultrasonic frequency of 45 kHz. The mixture was then rotary evaporated for 1.5 h at a temperature of 70 °C and a pressure of 0.08 MPa to remove moisture. The mixture was dried at a temperature of 110 °C for 11 h, then calcined at 470 °C for 5 h, and finally reduced at 390 °C for 2.5 h in a hydrogen atmosphere to obtain a bifunctional catalyst.

[0054] Example 3 A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 145℃ and 200r / min for 0.5h, and then vacuum degassed at 150℃ and 8kPa for 1h to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas mixture (composed of hydrogen and nitrogen in a volume ratio of 1:6) and then fed into a fixed-bed reactor packed with a bifunctional catalyst. The reaction is carried out at a temperature of 340℃, a reaction pressure of 0.5MPa, and a liquid hourly space velocity of 2h⁻¹. -1 The reaction was carried out under the condition that the volume ratio of nitrogen to degassed material was 250:1 to obtain the reaction product. S3. The reaction products are mixed with hydrogen and fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the reaction proceeds at a temperature of 240℃, a hydrogen pressure of 7MPa, and a liquid hourly space velocity of 2.5h⁻¹. -1 The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 500:1 to obtain a hydrogenated saturated product. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus (including a first-stage and a second-stage scraped film evaporator connected in series) for fractionation. The evaporation temperature of the first-stage scraped film evaporator is controlled at 230℃, the vacuum degree is 15Pa, and the scraper speed is 250r / min. The evaporation temperature of the second-stage scraped film evaporator is controlled at 280℃, the vacuum degree is 4Pa, and the scraper speed is 300r / min. The remaining high-boiling-point heavy components are collected and granulated using a steel belt granulator. The dripping temperature is controlled at 175℃, and the water temperature in the cooling zone is controlled at 25℃. The granules are cooled and solidified into high-melting-point, high-viscosity Fischer-Tropsch wax.

[0055] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent and polystyrene cross-linked divinylbenzene as a macroporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent to be 45:8:4:140:7:12, dissolving tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride in 2 mol / L hydrochloric acid aqueous solution, then adding macroporous template agent and mesoporous template agent in sequence, stirring and hydrolyzing at 45°C for 2 h, then transferring to a reaction vessel for hydrothermal crystallization at 120°C for 30 h, washing the product alternately with deionized water and anhydrous ethanol until neutral, drying under vacuum at 100°C for 16 h, and calcining at 600°C for 4 h to remove the template agent, thus obtaining a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure; (2) An ultrasonic-assisted complexation co-impregnation method was adopted, and the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride, citric acid and hydrochloric acid aqueous solution was controlled to be 2:0.5:0.8:5:80. Chloroplatinic acid, perrhenic acid, stannous chloride and citric acid were dissolved together in 1 mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). The mixture was impregnated for 2 h at an ultrasonic power of 450 W and an ultrasonic frequency of 50 kHz. The mixture was then rotary evaporated for 1 h at a temperature of 80 °C and a pressure of 0.1 MPa to remove moisture. The mixture was dried at a temperature of 120 °C for 10 h, calcined at 480 °C for 4 h, and finally reduced at 400 °C for 2 h in a hydrogen atmosphere to obtain a bifunctional catalyst.

[0056] To verify the comprehensive performance of the high-melting-point, high-viscosity Fischer-Tropsch waxes prepared in Examples 1-3 of this invention, Comparative Examples 1-7 were set up, wherein: Comparative Example 1 Comparative Example 1 is the same as Example 1, except that step S2 is omitted, and the degassed material is directly subjected to hydrogenation treatment. Details are as follows: A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 125°C and 100 r / min for 1 hour, and then vacuum degassed at 130°C and 3 kPa for 2 hours to obtain the degassed material. S2. After mixing the degassed material with hydrogen, it is fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the mixture is heated at 220°C, with a hydrogen pressure of 5 MPa and a liquid hourly space velocity of 1.5 h⁻¹. -1 The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 400:1 to obtain a hydrogenated saturated product. S3. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus (including a first-stage and a second-stage scraped film evaporator connected in series) for fractionation. The evaporation temperature of the first-stage scraped film evaporator is controlled at 210℃, the vacuum degree is 8Pa, and the scraper speed is 150r / min. The evaporation temperature of the second-stage scraped film evaporator is controlled at 260℃, the vacuum degree is 2Pa, and the scraper speed is 200r / min. The remaining high-boiling-point heavy components are collected and granulated using a steel belt granulator. The dripping temperature is controlled at 165℃, and the water temperature in the cooling zone is controlled at 15℃. The granules are cooled and solidified into high-melting-point, high-viscosity Fischer-Tropsch wax.

[0057] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent and polystyrene cross-linked divinylbenzene as a macroporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent to be 35:6:3:120:3:8, dissolving tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride in 1 mol / L hydrochloric acid aqueous solution, then adding macroporous template agent and mesoporous template agent in sequence, stirring and hydrolyzing at 35°C for 4 h, then transferring to a reaction vessel and hydrothermally crystallizing at 100°C for 36 h, washing the product alternately with deionized water and anhydrous ethanol until neutral, drying under vacuum at 80°C for 20 h, and calcining at 500°C for 6 h to remove the template agent, thus obtaining a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure; (2) An ultrasonic-assisted complexation co-impregnation method was adopted, and the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride, citric acid and hydrochloric acid aqueous solution was controlled to be 1:0.3:0.4:3:60. Chloroplatinic acid, perrhenic acid, stannous chloride and citric acid were dissolved together in 0.5 mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). The mixture was impregnated for 4 h at an ultrasonic power of 350 W and an ultrasonic frequency of 40 kHz. The mixture was then rotary evaporated for 2 h at a temperature of 60 °C and a pressure of 0.05 MPa to remove moisture. The mixture was dried at a temperature of 100 °C for 12 h, calcined at 460 °C for 6 h, and finally reduced at 380 °C for 3 h in a hydrogen atmosphere to obtain a bifunctional catalyst.

[0058] Comparative Example 2 Comparative Example 2 is the same as Example 1, except that the active component of the bifunctional catalyst is different. Details are as follows: A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 125°C and 100 r / min for 1 hour, and then vacuum degassed at 130°C and 3 kPa for 2 hours to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas mixture (composed of hydrogen and nitrogen in a volume ratio of 1:4) and then fed into a fixed-bed reactor packed with a bifunctional catalyst. The reaction is carried out at a temperature of 300℃, a reaction pressure of 0.1MPa, and a liquid hourly space velocity of 1h. -1 The reaction was carried out under the condition that the volume ratio of nitrogen to degassed material was 150:1 to obtain the reaction product. S3. The reaction products are mixed with hydrogen and fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the reaction proceeds at a temperature of 220°C, a hydrogen pressure of 5 MPa, and a liquid hourly space velocity of 1.5 h⁻¹. -1 The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 400:1 to obtain a hydrogenated saturated product. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus (including a first-stage and a second-stage scraped film evaporator connected in series) for fractionation. The evaporation temperature of the first-stage scraped film evaporator is controlled at 210℃, the vacuum degree is 8Pa, and the scraper speed is 150r / min. The evaporation temperature of the second-stage scraped film evaporator is controlled at 260℃, the vacuum degree is 2Pa, and the scraper speed is 200r / min. The remaining high-boiling-point heavy components are collected and granulated using a steel belt granulator. The dripping temperature is controlled at 165℃, and the water temperature in the cooling zone is controlled at 15℃. The granules are cooled and solidified into high-melting-point, high-viscosity Fischer-Tropsch wax.

[0059] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent and polystyrene cross-linked divinylbenzene as a macroporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent to be 35:6:3:120:3:8, dissolving tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride in 1 mol / L hydrochloric acid aqueous solution, then adding macroporous template agent and mesoporous template agent in sequence, stirring and hydrolyzing at 35°C for 4 h, then transferring to a reaction vessel and hydrothermally crystallizing at 100°C for 36 h, washing the product alternately with deionized water and anhydrous ethanol until neutral, drying under vacuum at 80°C for 20 h, and calcining at 500°C for 6 h to remove the template agent, thus obtaining a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure; (2) Using the ultrasonic-assisted complexation co-impregnation method, the mass ratio of chloroplatinic acid, stannous chloride, citric acid and hydrochloric acid aqueous solution was controlled to be 1:0.7:3:60. Chloroplatinic acid, stannous chloride and citric acid were dissolved together in 0.5 mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). The mixture was impregnated for 4 h at an ultrasonic power of 350 W and an ultrasonic frequency of 40 kHz. The mixture was then rotary evaporated for 2 h at a temperature of 60 °C and a pressure of 0.05 MPa to remove moisture. The mixture was dried at 100 °C for 12 h, calcined at 460 °C for 6 h, and finally reduced at 380 °C for 3 h in a hydrogen atmosphere to obtain a bifunctional catalyst.

[0060] Comparative Example 3 Comparative Example 3 is the same as Example 1, except that the active component of the bifunctional catalyst is different. Details are as follows: A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 125°C and 100 r / min for 1 hour, and then vacuum degassed at 130°C and 3 kPa for 2 hours to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas mixture (composed of hydrogen and nitrogen in a volume ratio of 1:4) and then fed into a fixed-bed reactor packed with a bifunctional catalyst. The reaction is carried out at a temperature of 300℃, a reaction pressure of 0.1MPa, and a liquid hourly space velocity of 1h. -1 The reaction was carried out under the condition that the volume ratio of nitrogen to degassed material was 150:1 to obtain the reaction product. S3. The reaction products are mixed with hydrogen and fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the reaction proceeds at a temperature of 220°C, a hydrogen pressure of 5 MPa, and a liquid hourly space velocity of 1.5 h⁻¹. -1 The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 400:1 to obtain a hydrogenated saturated product. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus (including a first-stage and a second-stage scraped film evaporator connected in series) for fractionation. The evaporation temperature of the first-stage scraped film evaporator is controlled at 210℃, the vacuum degree is 8Pa, and the scraper speed is 150r / min. The evaporation temperature of the second-stage scraped film evaporator is controlled at 260℃, the vacuum degree is 2Pa, and the scraper speed is 200r / min. The remaining high-boiling-point heavy components are collected and granulated using a steel belt granulator. The dripping temperature is controlled at 165℃, and the water temperature in the cooling zone is controlled at 15℃. The granules are cooled and solidified into high-melting-point, high-viscosity Fischer-Tropsch wax.

[0061] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent and polystyrene cross-linked divinylbenzene as a macroporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent to be 35:6:3:120:3:8, dissolving tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride in 1 mol / L hydrochloric acid aqueous solution, then adding macroporous template agent and mesoporous template agent in sequence, stirring and hydrolyzing at 35°C for 4 h, then transferring to a reaction vessel and hydrothermally crystallizing at 100°C for 36 h, washing the product alternately with deionized water and anhydrous ethanol until neutral, drying under vacuum at 80°C for 20 h, and calcining at 500°C for 6 h to remove the template agent, thus obtaining a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure; (2) Using the ultrasonic-assisted complexation co-impregnation method, the mass ratio of chloroplatinic acid, perrhenic acid, citric acid and hydrochloric acid aqueous solution was controlled to be 1:0.7:3:60. Chloroplatinic acid, perrhenic acid and citric acid were dissolved together in 0.5 mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). The mixture was impregnated for 4 h at an ultrasonic power of 350 W and an ultrasonic frequency of 40 kHz. The mixture was then rotary evaporated for 2 h at a temperature of 60 °C and a pressure of 0.05 MPa to remove moisture. The mixture was dried at a temperature of 100 °C for 12 h, calcined at 460 °C for 6 h, and finally reduced at 380 °C for 3 h in a hydrogen atmosphere to obtain a bifunctional catalyst.

[0062] Comparative Example 4 Comparative Example 4 is the same as Example 1, except that the preparation process of the bifunctional catalyst support is different. In Comparative Example 4, no polystyrene crosslinked divinylbenzene macroporous template agent was added during the preparation of the support. Details are as follows: A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 125°C and 100 r / min for 1 hour, and then vacuum degassed at 130°C and 3 kPa for 2 hours to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas mixture (composed of hydrogen and nitrogen in a volume ratio of 1:4) and then fed into a fixed-bed reactor packed with a bifunctional catalyst. The reaction is carried out at a temperature of 300℃, a reaction pressure of 0.1MPa, and a liquid hourly space velocity of 1h. -1 The reaction was carried out under the condition that the volume ratio of nitrogen to degassed material was 150:1 to obtain the reaction product. S3. The reaction products are mixed with hydrogen and fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the reaction proceeds at a temperature of 220°C, a hydrogen pressure of 5 MPa, and a liquid hourly space velocity of 1.5 h⁻¹. -1The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 400:1 to obtain a hydrogenated saturated product. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus (including a first-stage and a second-stage scraped film evaporator connected in series) for fractionation. The evaporation temperature of the first-stage scraped film evaporator is controlled at 210℃, the vacuum degree is 8Pa, and the scraper speed is 150r / min. The evaporation temperature of the second-stage scraped film evaporator is controlled at 260℃, the vacuum degree is 2Pa, and the scraper speed is 200r / min. The remaining high-boiling-point heavy components are collected and granulated using a steel belt granulator. The dripping temperature is controlled at 165℃, and the water temperature in the cooling zone is controlled at 15℃. The granules are cooled and solidified into high-melting-point, high-viscosity Fischer-Tropsch wax.

[0063] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution and mesoporous template agent to be 35:6:3:120:8, dissolving tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride in 1 mol / L hydrochloric acid aqueous solution, then adding the mesoporous template agent, stirring and hydrolyzing at 35°C for 4 h, then transferring to a reaction vessel and hydrothermally crystallizing at 100°C for 36 h, the product was washed alternately with deionized water and anhydrous ethanol until neutral, vacuum dried at 80°C for 20 h, and then calcined at 500°C for 6 h to remove the template agent, thus obtaining a zirconium-doped aluminum silicate molecular sieve support with a mesoporous channel structure; (2) An ultrasonic-assisted complexation co-impregnation method was adopted, and the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride, citric acid and hydrochloric acid aqueous solution was controlled to be 1:0.3:0.4:3:60. Chloroplatinic acid, perrhenic acid, stannous chloride and citric acid were dissolved together in 0.5 mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous channel structure obtained in step (1). The mixture was impregnated for 4 h at an ultrasonic power of 350 W and an ultrasonic frequency of 40 kHz. The mixture was then rotary evaporated for 2 h at a temperature of 60 °C and a pressure of 0.05 MPa to remove moisture. The mixture was dried at a temperature of 100 °C for 12 h, calcined at 460 °C for 6 h, and finally reduced at 380 °C for 3 h in a hydrogen atmosphere to obtain a bifunctional catalyst.

[0064] Comparative Example 5 Comparative Example 5 is the same as Example 1, except that the preparation process of the bifunctional catalyst support is different; zirconium oxychloride was not added for doping during the preparation of the support. Details are as follows: A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 125°C and 100 r / min for 1 hour, and then vacuum degassed at 130°C and 3 kPa for 2 hours to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas mixture (composed of hydrogen and nitrogen in a volume ratio of 1:4) and then fed into a fixed-bed reactor packed with a bifunctional catalyst. The reaction is carried out at a temperature of 300℃, a reaction pressure of 0.1MPa, and a liquid hourly space velocity of 1h. -1 The reaction was carried out under the condition that the volume ratio of nitrogen to degassed material was 150:1 to obtain the reaction product. S3. The reaction products are mixed with hydrogen and fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the reaction proceeds at a temperature of 220°C, a hydrogen pressure of 5 MPa, and a liquid hourly space velocity of 1.5 h⁻¹. -1 The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 400:1 to obtain a hydrogenated saturated product. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus (including a first-stage and a second-stage scraped film evaporator connected in series) for fractionation. The evaporation temperature of the first-stage scraped film evaporator is controlled at 210℃, the vacuum degree is 8Pa, and the scraper speed is 150r / min. The evaporation temperature of the second-stage scraped film evaporator is controlled at 260℃, the vacuum degree is 2Pa, and the scraper speed is 200r / min. The remaining high-boiling-point heavy components are collected and granulated using a steel belt granulator. The dripping temperature is controlled at 165℃, and the water temperature in the cooling zone is controlled at 15℃. The granules are cooled and solidified into high-melting-point, high-viscosity Fischer-Tropsch wax.

[0065] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent and polystyrene cross-linked divinylbenzene as a macroporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent to be 35:6:120:3:8, dissolving tetraethyl orthosilicate and aluminum isopropoxide in 1 mol / L hydrochloric acid aqueous solution, then adding macroporous template agent and mesoporous template agent in sequence, stirring and hydrolyzing at 35°C for 4 h, then transferring to a reaction vessel for hydrothermal crystallization at 100°C for 36 h, washing the product alternately with deionized water and anhydrous ethanol until neutral, drying under vacuum at 80°C for 20 h, and calcining at 500°C for 6 h to remove the template agent, thus obtaining a zirconium-doped aluminum silicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure; (2) An ultrasonic-assisted complexation co-impregnation method was adopted, and the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride, citric acid and hydrochloric acid aqueous solution was controlled to be 1:0.3:0.4:3:60. Chloroplatinic acid, perrhenic acid, stannous chloride and citric acid were dissolved together in 0.5 mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). The mixture was impregnated for 4 h at an ultrasonic power of 350 W and an ultrasonic frequency of 40 kHz. The mixture was then rotary evaporated for 2 h at a temperature of 60 °C and a pressure of 0.05 MPa to remove moisture. The mixture was dried at a temperature of 100 °C for 12 h, calcined at 460 °C for 6 h, and finally reduced at 380 °C for 3 h in a hydrogen atmosphere to obtain a bifunctional catalyst.

[0066] Comparative Example 6 Comparative Example 6 is the same as Example 1, except that the active component of the bifunctional catalyst is supported differently; citric acid was not added for complexation. Details are as follows: A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 125°C and 100 r / min for 1 hour, and then vacuum degassed at 130°C and 3 kPa for 2 hours to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas mixture (composed of hydrogen and nitrogen in a volume ratio of 1:4) and then fed into a fixed-bed reactor packed with a bifunctional catalyst. The reaction is carried out at a temperature of 300℃, a reaction pressure of 0.1MPa, and a liquid hourly space velocity of 1h. -1 The reaction was carried out under the condition that the volume ratio of nitrogen to degassed material was 150:1 to obtain the reaction product. S3. The reaction products are mixed with hydrogen and fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the reaction proceeds at a temperature of 220°C, a hydrogen pressure of 5 MPa, and a liquid hourly space velocity of 1.5 h⁻¹. -1 The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 400:1 to obtain a hydrogenated saturated product. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus (including a first-stage and a second-stage scraped film evaporator connected in series) for fractionation. The evaporation temperature of the first-stage scraped film evaporator is controlled at 210℃, the vacuum degree is 8Pa, and the scraper speed is 150r / min. The evaporation temperature of the second-stage scraped film evaporator is controlled at 260℃, the vacuum degree is 2Pa, and the scraper speed is 200r / min. The remaining high-boiling-point heavy components are collected and granulated using a steel belt granulator. The dripping temperature is controlled at 165℃, and the water temperature in the cooling zone is controlled at 15℃. The granules are cooled and solidified into high-melting-point, high-viscosity Fischer-Tropsch wax.

[0067] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent and polystyrene cross-linked divinylbenzene as a macroporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent to be 35:6:3:120:3:8, dissolving tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride in 1 mol / L hydrochloric acid aqueous solution, then adding macroporous template agent and mesoporous template agent in sequence, stirring and hydrolyzing at 35°C for 4 h, then transferring to a reaction vessel and hydrothermally crystallizing at 100°C for 36 h, washing the product alternately with deionized water and anhydrous ethanol until neutral, drying under vacuum at 80°C for 20 h, and calcining at 500°C for 6 h to remove the template agent, thus obtaining a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure; (2) Using the ultrasonic-assisted complexation co-impregnation method, the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride and hydrochloric acid aqueous solution was controlled to be 1:0.3:0.4:63. Chloroplatinic acid, perrhenic acid and stannous chloride were dissolved together in 0.5mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). The mixture was impregnated for 4h under ultrasonic power of 350W and ultrasonic frequency of 40kHz. The mixture was then rotary evaporated for 2h under the conditions of 60℃ and 0.05MPa to remove moisture. The mixture was dried at 100℃ for 12h, calcined at 460℃ for 6h, and finally reduced at 380℃ for 3h under hydrogen atmosphere to obtain a bifunctional catalyst.

[0068] Comparative Example 7 Comparative Example 7 is the same as Example 1, except that the separation and purification method is different; the multi-stage short-path molecular distillation in step S4 is replaced with vacuum distillation. Specifically: A high-melting-point, high-viscosity Fischer-Tropsch wax is prepared by the following method: S1. The Fischer-Tropsch wax raw material is heated and melted at 125°C and 100 r / min for 1 hour, and then vacuum degassed at 130°C and 3 kPa for 2 hours to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas mixture (composed of hydrogen and nitrogen in a volume ratio of 1:4) and then fed into a fixed-bed reactor packed with a bifunctional catalyst. The reaction is carried out at a temperature of 300℃, a reaction pressure of 0.1MPa, and a liquid hourly space velocity of 1h. -1 The reaction was carried out under the condition that the volume ratio of nitrogen to degassed material was 150:1 to obtain the reaction product. S3. The reaction products are mixed with hydrogen and fed into a fixed-bed hydrogenation reactor. Under the action of a nickel-molybdenum catalyst, the reaction proceeds at a temperature of 220°C, a hydrogen pressure of 5 MPa, and a liquid hourly space velocity of 1.5 h⁻¹. -1The hydrogenation reaction was carried out under the condition of a hydrogen-to-oil volume ratio of 400:1 to obtain a hydrogenated saturated product. S4. The hydrogenated saturated product is introduced into a vacuum distillation column and separated under low vacuum conditions of 260℃ and 2kPa. The distillation time of the bottom material is controlled to be 3h. The bottom residue is collected and granulated using a steel belt granulator. The dripping temperature is controlled to be 165℃ and the water temperature in the cooling zone is 15℃. The product is cooled and solidified into granules to obtain high melting point and high viscosity Fischer-Tropsch wax.

[0069] The bifunctional catalyst is prepared by the following method: (1) Using hexadecyltrimethylammonium bromide as a mesoporous template agent and polystyrene cross-linked divinylbenzene as a macroporous template agent; controlling the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent to be 35:6:3:120:3:8, dissolving tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride in 1 mol / L hydrochloric acid aqueous solution, then adding macroporous template agent and mesoporous template agent in sequence, stirring and hydrolyzing at 35°C for 4 h, then transferring to a reaction vessel and hydrothermally crystallizing at 100°C for 36 h, washing the product alternately with deionized water and anhydrous ethanol until neutral, drying under vacuum at 80°C for 20 h, and calcining at 500°C for 6 h to remove the template agent, thus obtaining a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure; (2) An ultrasonic-assisted complexation co-impregnation method was adopted, and the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride, citric acid and hydrochloric acid aqueous solution was controlled to be 1:0.3:0.4:3:60. Chloroplatinic acid, perrhenic acid, stannous chloride and citric acid were dissolved together in 0.5 mol / L hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution was mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). The mixture was impregnated for 4 h at an ultrasonic power of 350 W and an ultrasonic frequency of 40 kHz. The mixture was then rotary evaporated for 2 h at a temperature of 60 °C and a pressure of 0.05 MPa to remove moisture. The mixture was dried at a temperature of 100 °C for 12 h, calcined at 460 °C for 6 h, and finally reduced at 380 °C for 3 h in a hydrogen atmosphere to obtain a bifunctional catalyst.

[0070] The comprehensive properties of the high melting point and high viscosity Fischer-Tropsch waxes in Examples 1-3 and Comparative Examples 1-7 of this invention were tested respectively.

[0071] (1) Melting point: Tested according to ASTM D87 standard, unit is °C.

[0072] (2) Kinematic viscosity: The kinematic viscosity of the Fischer-Tropsch wax sample at 140°C was measured according to ASTM D445 standard, and the unit is mm. 2 / s.

[0073] (3) Penetration: The penetration of the Fischer-Tropsch wax sample at 25°C was measured according to ASTM D1321 standard. The smaller the value, the higher the hardness. The unit is 0.1 mm (dmm).

[0074] (4) T-type peel strength: The Fischer-Tropsch wax sample and commercially available EVA hot melt resin (brand: Taiwan Polymer, grade: UE612-04, VA content: 19%) were mixed at a mass ratio of 1:4 and stirred at 500 rpm for 30 min at 160℃ to make them melt and mix evenly, thus preparing a hot melt adhesive sample. The coating was applied between two layers of PET film using a coater, with the coating thickness controlled at 50 μm. Then, it was transferred to a hot press for pressing, with the pressing temperature controlled at 150℃, the pressing pressure at 0.3 MPa, and the pressing time at 3 min. After being removed, it was cooled and cured at room temperature (25℃) for 72 h. The average peel force under constant tension was then tested on a universal testing machine using the 180° peel method, with the unit being N / cm.

[0075] The test results are shown in Table 1: Table 1: Comprehensive performance test data of high melting point and high viscosity Fischer-Tropsch wax in Examples 1-3 and Comparative Examples 1-7

[0076] As shown in Table 1, the high melting point and high viscosity Fischer-Tropsch waxes prepared in Examples 1-3 of this invention have significantly better overall performance than Comparative Examples 1-7.

[0077] As can be seen from Example 1 and Comparative Example 1, Comparative Example 1 did not undergo a catalytic dehydrogenation micro-crosslinking reaction. Although its product retained the straight-chain heavy components through short-path molecular distillation and possessed a high melting point of 122.5°C, its carbon chains maintained a highly linear structure, with no physical entanglement between molecular chains. This resulted in a low kinematic viscosity in the molten state and difficulty in forming a network with the polymer substrate, leading to low T-peel strength. In contrast, Example 1, through a micro-crosslinking reaction, improved the kinematic viscosity and peel strength of the product while maintaining the crystalline melting point.

[0078] As can be seen from Example 1 and Comparative Example 2, in Comparative Example 2, the Re component in the bifunctional catalyst was replaced with an equal mass of Sn component. Although the total mass of the catalyst metal loading remained unchanged, the absence of Re led to a decrease in the anti-carbon deposition ability of the noble metal component. The catalyst was prone to reduced activity in the heavy wax reaction system due to surface carbon deposition, resulting in insufficient dehydrogenation and micro-crosslinking transformation of long molecular chains. Ultimately, this resulted in the kinematic viscosity and peel strength of the product being lower than those of Example 1.

[0079] As shown in Example 1 and Comparative Example 3, in Comparative Example 3, the Sn component in the bifunctional catalyst was replaced with an equal mass of the Re component. Although an anti-carbon deposition component was added, the lack of Sn's moderating effect on the d-band electronic structure of Pt meant that Pt's hydrogenolysis activity on the C-C bonds was not effectively suppressed, leading to chain cleavage reactions in long-chain alkanes during dehydrogenation. This resulted in a decrease in the molecular weight of the product, leading to a significant decrease in the macroscopic melting point and an increase in penetration.

[0080] As can be seen from Example 1 and Comparative Example 4, no polystyrene crosslinking divinylbenzene macroporous template agent was added in the catalyst support preparation of Comparative Example 4. Due to the lack of hierarchical macroporous structure of the support, long-chain alkane molecules face greater steric hindrance when entering pure mesoporous channels, limiting molecular diffusion and resulting in reduced micro-crosslinking reaction efficiency. Consequently, the kinematic viscosity and peel strength of the product are lower than those of Example 1.

[0081] As shown in Example 1 and Comparative Example 5, the catalyst support in Comparative Example 5 was not doped with zirconium oxychloride. Due to the lack of zirconium to regulate the acidity of the molecular sieve, the support surface had many strong Brønsted acid sites, which triggered acid-catalyzed cracking reactions. The fracture of the heavy alkane skeleton led to a decrease in the melting point of the final product, as well as a reduction in kinematic viscosity and exfoliation strength.

[0082] As can be seen from Example 1 and Comparative Example 6, no citric acid complexing agent was added to the impregnation solution in Comparative Example 6. The dispersion of the metal precursor decreased during the co-impregnation and reduction processes, leading to the easy aggregation of the active components. This reduced the density of effective catalytic active sites, resulting in a decrease in the dehydrogenation and micro-crosslinking conversion efficiency, and the performance indicators of the final product were inferior to those of Example 1.

[0083] As shown in Example 1 and Comparative Example 7, Comparative Example 7 used vacuum distillation instead of multi-stage short-path molecular distillation. Due to the limited operating vacuum of vacuum distillation, the gas-liquid separation efficiency is far lower than that of molecular-level short-path distillation, resulting in the incomplete removal of some light and medium components with plasticizing effects remaining in the product. Furthermore, the long residence time and prolonged heating history of the material in the reboiler led to slight thermal depolymerization of the cross-linked macromolecular network. The combined effect of the residual light components and the slight degradation of the macromolecules weakened the physical entanglement effect of the heavy wax, resulting in the final product's melting point and viscosity failing to reach the levels of the examples, while the penetration also increased.

[0084] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A method for preparing a high-melting-point, high-viscosity Fischer-Tropsch wax, characterized in that, Includes the following steps: S1. The Fischer-Tropsch wax raw material is heated, melted, and then degassed under vacuum to obtain the degassed material. S2. The degassed material is mixed with a hydrogen-containing carrier gas and fed into a fixed-bed reactor packed with a bifunctional catalyst to react and obtain the reaction product. S3. After mixing the reaction products with hydrogen, the mixture is fed into a fixed-bed hydrogenation reactor and hydrogenation reaction is carried out under the action of a hydrogenation saturated catalyst to obtain hydrogenation saturated products. S4. The hydrogenated saturated product is introduced into a multi-stage short-path molecular distillation apparatus for fractionation, and the remaining high-boiling-point heavy components are collected, cooled and shaped to obtain high-melting-point, high-viscosity Fischer-Tropsch wax. In step S2, the bifunctional catalyst includes a zirconium-doped aluminosilicate molecular sieve support with a mesoporous-macroporous hierarchical pore structure, and a Pt-Re-Sn ternary active component loaded on the support. The bifunctional catalyst was prepared by the following method: (1) Tetraethyl orthosilicate, aluminum isopropoxide and zirconium oxychloride are dissolved in hydrochloric acid aqueous solution, and then macroporous template agent and mesoporous template agent are added in sequence. After stirring and hydrolyzing at 35-45℃ for 2-4h, the mixture is transferred to a reaction vessel and hydrothermally crystallized at 100-120℃ for 30-36h. The product is washed, dried and calcined to obtain zirconium-doped aluminum silicate molecular sieve support with mesoporous-macroporous hierarchical pore structure. (2) Chloroplatinic acid, perrhenic acid, stannous chloride and citric acid are dissolved together in hydrochloric acid aqueous solution to prepare an impregnation solution. The impregnation solution is ultrasonically impregnated and mixed with the zirconium-doped aluminosilicate molecular sieve support with mesoporous-macroporous hierarchical pore structure obtained in step (1). After rotary evaporation, drying and calcination and reduction, a bifunctional catalyst is obtained. In step (1), the mass ratio of tetraethyl orthosilicate, aluminum isopropoxide, zirconium oxychloride, hydrochloric acid aqueous solution, macroporous template agent and mesoporous template agent is 35-45:6-8:3-4:120-140:3-7:8-12. In step (2), the mass ratio of chloroplatinic acid, perrhenic acid, stannous chloride, citric acid, and hydrochloric acid aqueous solution is 1-2:0.3-0.5:0.4-0.8:3-5:60-80; In step S2, the reaction conditions are: temperature 300-340℃, reaction pressure 0.1-0.5MPa, and liquid hourly space velocity 1-2h. -1 The volume ratio of hydrogen-containing mixed carrier gas to degassed material is 150-250:

1.

2. The method for preparing high-melting-point, high-viscosity Fischer-Tropsch wax according to claim 1, characterized in that, In step S1, the heating and melting conditions are: temperature 125-145℃, stirring speed 100-200r / min, and heating time 0.5-1h.

3. The method for preparing high-melting-point, high-viscosity Fischer-Tropsch wax according to claim 1, characterized in that, In step S1, the vacuum degassing conditions are: temperature 130-150℃, vacuum degree 3-8kPa, and degassing time 1-2h.

4. The method for preparing high-melting-point, high-viscosity Fischer-Tropsch wax according to claim 1, characterized in that, In step S3, the hydrogenation reaction conditions are: temperature 220-240℃, hydrogen pressure 5-7 MPa, and liquid hourly space velocity 1.5-2.5 h⁻¹. -1 The hydrogen-to-oil volume ratio is 400-500:

1.

5. A high-melting-point, high-viscosity Fischer-Tropsch wax, characterized in that, It is prepared by the method for preparing high melting point and high viscosity Fischer-Tropsch wax according to any one of claims 1-4.

Citation Information

Patent Citations

  • Method for preparing catalyst for lubricant base oil by Fischer-tropsch light component wax and application

    CN108031486A

  • Processing method of Fischer-Tropsch wax

    CN111978982A